Understanding the Experiences and Processes of Health Canada's Evacuation Policy for Pregnant First Nations Women in Manitoba - Lawford, Karen (Université d'Ottawa / University of Ottawa, 2017)
First Nations women who live on reserves receive maternity care from a variety of government health care systems: Federal, provincial, and municipal. At first glance, this seems like an abundant amount of health care; however, the lack of coordination has led to poorer outcomes as demonstrated for example by the twofold IMR for First Nations on reserves compared to that of non-Aboriginal populations. To inform discussions and changes to health care policy and programming for maternity care for First Nations on reserves, my dissertation focuses on Health Canada’s evacuation policy within the province of Manitoba. It describes how First Nations women journey among these three health care systems in the provision of that care. This federal policy instructs federally employed nurses to arrange for the transfer of pregnant First Nations women who live on rural and remote reserves to an urban – and usually southern – location so that the women can receive labour and birthing services. Women are evacuated out of their home communities between 36 and 38 weeks gestational age and wait in the city, often alone, for labour to start. While there is a general understanding of how different elements of this federal policy work, there is no literature that describes its execution in detail nor in full. To address this critical knowledge gap, my dissertation consists of three stand-alone papers. For the first paper, “‘This Policy Sucks and It’s Stupid:’ Mapping Maternity Care for First Nations Women on Reserves in Manitoba,” I used intersectionality, institutional ethnography, and semi-structured interviews to produce a descriptive and visual map of the evacuation policy. Using intersectionality and a case study approach, the second paper, “Health Canada’s Evacuation Policy for Pregnant First Nations Women in Manitoba: Resignation, Resilience, and Resistance,” semi-structured interview data are analyzed through a thematic analysis to understand the experiences and perspectives of First Nations women, family, and community members. I argue for the development of a specific theoretical framework that makes explicit the specific legal and policy influences particular to First Nations women who live on reserves in the third paper, “The Legal Categorization of First Nations Women in Health: The Need for a First Nations Feminist Theory.” Taken as a whole, these three papers address some of the knowledge gaps related to maternity care services for First Nations women once they are evacuated. They also situate these gaps within the legal context of health care for First Nations women so that tangible improvements can be made.
Keywords: First Nations; maternity care; policy; evacuation policy; health; on reservesr